Effect of tool geometry on dimensional accuracy and surface finish of turned parts - Islam, Mohammad Nazrul; Gharh, B.; Pramanik, Alokesh (UTM Razak School, 2013)
This paper investigates, experimentally and analytically, the influence of tool geometry on two major dimensional accuracy characteristics of a turned part—diameter error and circularity—and the surface finish characteristic arithmetic average. Data were analysed via two methods: Pareto ANOVA and Taguchi method. The findings indicate that the two selected tool geometry parameters—insert shape and nose radius—have a considerable effect on diameter error (total contribution 67.0%) and minor effects on surface finish (total contribution 11.6%) and circularity (total contribution 7.5%). The major contributor to surface finish is feed rate, whereas circularity is dominated by interaction effects.